Female performances and representation in the Hollywood musical, 1929 - 1940 - Barrett, Ciara (Trinity College (Dublin, Ireland). Department of Film, 2015)
This thesis explores the evolution of female performance paradigms and representation in Hollywood musicals from 1929 to 1940. In particular, it considers how the paradigmatic representation of femininity within the musical was influenced by the implementation of film censorship under the Production Code Administration and specifically how the application of Code policy to the regulation of female performance and representation in the Hollywood musical impacted the structural development of the genre more broadly.
Keywords: Drama, Film & Music, Ph.D.; Ph.D. Trinity College Dublin